LOOKING FOR A NEW PARADIGM IN COPYRIGHT IN INDONESIAN REGULATIONS - Nainggolan, Bernard (Jurnal Pembaharuan Hukum, 2023)
This research examines the copyright landscape in Indonesia with a focus on regulatory dynamics, public awareness and law enforcement. The research approach uses normative methods and literature reviews to examine the development of copyright law, public moral awareness, and the implementation of policies related to copyright protection. Despite progress in copyright regulations, research shows that copyright infringement remains a serious problem in Indonesia. Piracy practices are still common and accepted as a cultural norm, while copyright law enforcement faces challenges in increasing public awareness and enforcement effectiveness. The findings of this research highlight the urgency of education to increase public awareness about copyright. The importance of further action to strengthen law enforcement and effectively protect copyright in Indonesia was also emphasized. This research has important implications for policy makers, law enforcers, and the general public to increase understanding of copyright, change cultural norms regarding piracy, and increase awareness of the importance of protecting copyright for sustainable social and economic development in Indonesia.